COUNSELING ABOUT THE IMPACT OF STUNTING ON TODDLERS: COUNSELING ABOUT THE IMPACT OF STUNTING ON TODDLERS - Ginting Munthe, Novita Br; Sembiring, Iskandar Markus; Safitri, Riri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2022)
high incidence of stunting. Stunting is a chronic condition that can be seen from stunted growth due to malnutrition that occurs over a long period of time. Currently, the incidence of stunting in children under five is around 162 million. If this incident continues, it is estimated that by 2025 there will be an additional number of children experiencing stunting, namely around 127 million children. Therefore, it is necessary to provide counseling to mothers of toddlers regarding what factors can cause stunting to be able to anticipate that their children will experience stunting. The purpose of this community service activity (PKM) is to identify how knowledgeable mothers are about the impact of stunting on toddlers. This activity was carried out in November for 2 days by distributing questionnaires before and after counseling which aimed to find out mother's knowledge about the impact of stunting on toddlers. The results of the PKM showed that before the counseling activities were carried out, the majority of the knowledge of mothers under five was in the sufficient category, namely 46.4% and after the extension activities, the majority of knowledge of mothers under five was good, namely 71.4%. It is recommended that mothers and families pay attention to the growth and development of their children and provide adequate nutrition to meet the nutritional intake of children, so that the incidence of stunting in children under five can be avoided and the growth and development of children. develop perfectly and become the next generation of intelligent nation.